Broken pottery in a filled room: the case of service areas in the “central baths” of Nora (CA) - Panero, Elisa; Messina, Claudia; Zollo , Francesca (Rei Cretariae Romanae Fautorum Acta, 2015)
The central area of Nora (the “Area E”) is a very complex district because, in a chronological period of at least eight centuries, residential and public buildings (baths, theater) alternate, covering a period of time ranging from late Punic facies to Late Antiquity.